Learning while setting precedents - Ying Chen; Hülya Eraslan (Koç University-TÜSİAD Economic Research Forum (ERF), 2018)
A decision maker (DM) must address a series of problems over time. Each period, a random case arises and the DM must make a yes-or-no decision, which we call a ruling. She is uncertain about the correct ruling until she conducts a costly investigation. A ruling establishes a precedent, which may be costly to violate in the future. We compare the DM's incentive to acquire information, the evolution of standards and the social welfare under two institutions: nonbinding precedent and binding precedent. Under nonbinding precedent, the DM is not required to follow previous rulings, but under binding precedent, she must follow previous rulings where applicable. We find that, compared to nonbinding precedent, the incentive for information acquisition is stronger under binding precedent in earlier periods when few precedents exist, but as more precedents are established over time, the incentive for information acquisition becomes weaker under binding precedent. Even though erroneous rulings may be perpetuated under binding precedent, social welfare can be higher because of the more intensive investigation conducted early on.
Keywords: D02; D23; D83; K4; 330; precedent; binding precedent; information acquisition; transparency